2021
DOI: 10.3389/fimmu.2021.675751
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Synthase Kinase 3β Modulates the Inflammatory Response Activated by Bacteria, Viruses, and Parasites

Abstract: Knowledge of glycogen synthase kinase 3β (GSK3β) activity and the molecules identified that regulate its function in infections caused by pathogenic microorganisms is crucial to understanding how the intensity of the inflammatory response can be controlled in the course of infections. In recent years many reports have described small molecular weight synthetic and natural compounds, proteins, and interference RNA with the potential to regulate the GSK3β activity and reduce the deleterious effects of the inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 102 publications
(111 reference statements)
1
16
0
Order By: Relevance
“…However, the fact that GSK-3β expression was upregulated in mouse brain but not in cultured neuronal cells suggests that the upregulation of GSK-3β is not directly mediated by LRRK2. Since it has been reported that GSK-3β expression is promoted by tumor necrosis factor-α (TNF-α) 9) and that LRRK2 upregulates TNF-α via activation of TLR4, 10) thus we speculate that overexpression of LRRK2 in mouse brain increases GSK-3β expression via the TLR4-meditaed TNF-α production. In fact, mRNA level of inflammatory cytokines including of TNF-α was increased in LRRK2 transgenic mouse brain under the experimental conditions (Supplementary material 2).…”
Section: Resultsmentioning
confidence: 88%
“…However, the fact that GSK-3β expression was upregulated in mouse brain but not in cultured neuronal cells suggests that the upregulation of GSK-3β is not directly mediated by LRRK2. Since it has been reported that GSK-3β expression is promoted by tumor necrosis factor-α (TNF-α) 9) and that LRRK2 upregulates TNF-α via activation of TLR4, 10) thus we speculate that overexpression of LRRK2 in mouse brain increases GSK-3β expression via the TLR4-meditaed TNF-α production. In fact, mRNA level of inflammatory cytokines including of TNF-α was increased in LRRK2 transgenic mouse brain under the experimental conditions (Supplementary material 2).…”
Section: Resultsmentioning
confidence: 88%
“…Glucose transporter 4 (GLUT4) is transported to the neuron membrane under the induction of Akt, which improves insulin transport to brain neurons in learning and memory state [23]. Akt also regulates phosphorylation and deactivation of glycogen synthase kinase 3β (GSK-3β), which on the one hand reduces apoptosis signaling in cells, on the other hand, it can also lead to insulin resistance and tau protein hyperphosphorylation, which is a key step in cognitive impairment [24,25,26]. Wnt signaling can regulate cell proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Hs GSK-3β was reported to modulate the inflammatory response activated by parasite infections, marked by a dramatic increase in cytokine production [ 48 ]. Cytokine storms are usually implicated in cerebral malaria and liver damage, which can be fatal without treatment [ 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%